A Qualitative Study on Digital Marketing and Market Penetration: Insights from Uganda's Insurance Practitioners - Perry Gamba; Jesse Doreen Naguyo Schilthuis (International Journal of Marketing and Digital Creative, 2026)
This study analyzes the impact of digital marketing on market penetration, with a specific focus on the insurance industry in Uganda. Through qualitative research utilizing semi-structured interviews with industry experts, this research examines how digital marketing strategies influence market penetration and business growth. The findings reveal that digital marketing significantly impacts market penetration through increased reach and targeting, cost-effectiveness, data-driven insights, improved client engagement, and enhanced measurement capabilities. The study contributes to the existing body of knowledge by providing empirical evidence on the relationship between digital marketing and market penetration, offering valuable insights for businesses seeking to expand their market presence through digital channels.